Pengembangan Multimedia Interaktif untuk Membantu Peserta Didik dalam Memahami Konsep Matematika pada Materi Transformasi Geometri Kelas XI MIPA SMA Negeri Benlutu - Ta'eko, Juldini Trinasti; Samo, Damianus D.; Halim, Fransiska A. (Griya Journal of Mathematics Education and Application, 2024)
During the learning of mathematics in SMA Negeri Benlutu, especially in class XI, teacher use WhatsApp group to send materials in .pdf format to students. Meanwhile, there is no sufficient learning media to support learning in the classroom. Therefore, the purpose of this study is to create interactive learning media, to help students understand valid, practical, and effective mathematical concepts about geometric transformation material in class XI MIPA SMA Negeri Benlutu. This research uses the research and development (R&D) method with the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. The instruments used are interviews, questionnaires, and concept understanding tests. The results showed that the ThransForMath application met the three criteria of learning media feasibility: valid, practical, and effective. Valid criteria were obtained from the average validity of three material and media experts, which reached 4,7, or in the "valid" category. Practical criteria are obtained from the average practicality of all students in small and large classes, which reached 4,74 and 4,83, respectively, or in the "practical" category. Effective criteria are obtained from the results of students' concept understanding tests in small and large class trials of 100% and 88%, respectively, or in the "effective" category.